VERBAL MOTIVATION: OPTIONS FOR PREVENTING DENTOFACIAL MALOCCLUSIONS AT THE AGE OF GROWTH: (MOTIVASI VERBAL: PILIHAN PENCEGAHAN MALOKLUSI DENTOFASIAL PADA USIA TUMBUH KEMBANG) - Widya Irsyad; Rudi Satria Darwis; Bayu Fajar Ilyasa; Maghfira Fitri Febriani (Journal of Health and Dental Sciences, 2022)
Good communication between dentists and patients will create success in the patient care process and help patients to improve their understanding of medical information, perceptions, and expectations. Interpersonal relationships between children, parents, and operators (Dentists), are part of the basic pattern of behavior management or orthodontic treatment in children. Treatment of anterior crossbite in mixed dentition is highly recommended because this malocclusion cannot be corrected with growth or age. Case Report: A 9-year-old child came with a complaint that her right upper front tooth was growing behind her lower front teeth, so she felt insecure when smiling and uncomfortable when biting. The patient's mother and the patient want a treatment that can return the teeth into a good and normal position. The patient had no history of disease either in childhood or at present. Dental history such as normal tooth eruption, premature loss, and dental trauma was denied but the patient stated that the permanent teeth had grown before the baby teeth fell out. The patient has no bad habits. In this case, education was carried out to the patient and his mother regarding the use of a tongue blade to push tooth 11 toward the labial direction to correct the palatoverted tooth 11. Conclusion: Cases of anterior crossbite in permanent teeth are quite common in children who are growing and developing, so early treatment to stimulate growth balance and occlusal development is needed to modify the growth direction to prevent further malocclusion. DOI : 10.54052/jhds.v2n1.p85-96